Heat pumps in aviation - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The paper discusses the general principle of energy conversion in open energy systems and presents the heat pump operating principle based on the molecular-kinetic theory. Various mechanisms of aircraft cooling during flight in the fixed atmosphere have been explained as well as the conditions in which electromagnetic systems can operate as heat pumps. It has been stated that the aircraft in flight represents a heat pump.